1983
DOI: 10.1055/s-2007-1018780
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Triiodothyronine on Insulin Binding and Action in Rat Adipocytes

Abstract: The effects of a short term (2 hour) incubation of 5 microM triiodothyronine (T3) on 125I-insulin binding and insulin stimulated (14C)-2-deoxy-D-glucose uptake in rat adipocytes was investigated. In the presence of 5 microM T3, (14C)-2-deoxy-D-glucose uptake was significantly decreased by 11 to 24% at insulin concentrations of 5 to 1000 microU/ml. The concentration of insulin eliciting a half maximal response for insulin stimulated (14C)-2-deoxy-D-glucose uptake was 11.5 microU/ml in the control, and 14.3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It seems that this general statement is not universal, particularly with regard to glucose utilization, since the tissue specific differences may occur. Czech and Amatruda (6) showed that in vitro addition of T3 to isolated adipocytes lowered both, the insulin receptors and glucose uptake as well.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that this general statement is not universal, particularly with regard to glucose utilization, since the tissue specific differences may occur. Czech and Amatruda (6) showed that in vitro addition of T3 to isolated adipocytes lowered both, the insulin receptors and glucose uptake as well.…”
Section: Resultsmentioning
confidence: 99%
“…These hormones are reduced or absent from decapitated pig serum [18] as are cate cholamines [unpublished data]. The absence of these potent insulin antagonists [3,4,13,22] during the developmental period of glu cose-sensitive insulin secretion [8] suggests that these insulin antagonists may contribute to the observed differences between tissues from decapitated and control animals as ges tation proceeds.…”
Section: Discussionmentioning
confidence: 99%